Evaluasi Program Pendidikan - Herdha, Romeo; Kurniawan, Rafli Firmansyah; Gading, Waming; Muttaqin, M. Irsyad; Amalia, Kaniati (TSAQOFAH, 2024)
Program evaluation is an activity that aims to collect information from an implementation and a process in an organization consisting of a group of people who participate in decision making. This research uses a literature review method from e-book journals. The purpose of this article is to help teachers in preparing evaluations in an educational program in a school institution. The results of our research, namely analysis of school program evaluation results, show the extent of school program achievements in the previous year. Various policies in the education sector are also presented as a reference for preparing evaluations. The results of this analysis are the starting point for evaluating school programs in previous and subsequent years as well as steps that supervisors must take.